2019
DOI: 10.3171/2019.8.focus19407
|View full text |Cite
|
Sign up to set email alerts
|

Significance of cerebrospinal fluid inflammatory markers for diagnosing external ventricular drain–associated ventriculitis in patients with severe traumatic brain injury

Abstract: ObjectiveThe aim of this study was to investigate the diagnostic potential of the inflammatory markers interleukin-6 (IL-6), total leukocyte count (TLC), and protein in the CSF and IL-6, C-reactive protein, and white blood cell count in the serum for the early diagnosis of ventriculitis in patients with traumatic brain injury (TBI) and an external ventricular drain compared with patients without ventriculitis.Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Important common complications associated with traumatic brain injury and critical care such as EVD-associated ventriculitis and sepsis were also under-reported. For example, only two cases of ventriculitis were reported in our review of 699 patients, compared to typical rates of 5–15% reported in the wider literature [ 60 62 ]. Such complications have previously been shown to significantly impact IL-6 concentrations in bodily fluids and therefore represent important confounders [ 60 , 63 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Important common complications associated with traumatic brain injury and critical care such as EVD-associated ventriculitis and sepsis were also under-reported. For example, only two cases of ventriculitis were reported in our review of 699 patients, compared to typical rates of 5–15% reported in the wider literature [ 60 62 ]. Such complications have previously been shown to significantly impact IL-6 concentrations in bodily fluids and therefore represent important confounders [ 60 , 63 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Elevated CSF levels of IL-6 have been well described in studies of community-acquired bacterial meningitis ( Prasad et al , 2014 ; García-Hernández et al , 2016 ; Srinivasan et al , 2016 ; Lepennetier et al , 2019 ; Liba et al , 2019 ), but not in all ( Asano et al , 2010 ), and IL-6 is also raised in encephalitis ( Morichi et al , 2018 ). Elevated IL-6 levels in CSF have not only been reported in nosocomial infections in patients with shunts and EVDs ( Asi-Bautista et al , 1997 ; Schoch et al , 2008 ; Lenski et al , 2019 , Skar et al , 2019 b ) but also in inflammation and vasospasm after subarachnoid haemorrhage ( Lenski et al , 2017 ), all combining to make it a poor differentiator between nosocomial infection and sterile neuroinflammation. EN-RAGE is produced by macrophages in response to IL-6 in vitro ( Hasegawa et al , 2003 ), and both EN-RAGE and IL-6 ( Chiaretti et al , 2008 ) have previously been noted as increased in serum or CSF, respectively, in response to cerebral trauma and during paediatric CNS infection when compared to controls ( Prasad et al , 2014 ; García-Hernández et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study [ 32 ], the level of IL-6 in the CSF of patients with a diagnosis of purulent bacterial meningitis with a more severe course reached 392 ± 199 pg/mL. Retrospective data [ 33 ] from patients with traumatic brain injury ( n = 40) and external ventricular drain-associated ventriculitis showed that the CSF IL-6 levels higher than the threshold of 4064 pg/mL were significantly associated with the probability of ventriculitis. In another prospective study [ 29 ], all patients with proven bacterial meningitis had CSF IL-6 more than 500 pg/mL.…”
Section: Discussionmentioning
confidence: 99%